2004
DOI: 10.1200/jco.2004.10.173
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Randomized Trial of Hyperfractionated Cranial Radiation Therapy for Treatment of High-Risk Acute Lymphoblastic Leukemia: Therapeutic Efficacy and Neurotoxicity

Abstract: HFX provides no benefit in terms of cognitive late effects and may compromise antileukemic efficacy. HFX should not be substituted for conventionally dosed CRT in children who require radiation therapy for treatment of acute lymphoblastic leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 23 publications
2
26
3
Order By: Relevance
“…Especially in children and young adults, there are late effects of IT chemotherapy and CRT on cognition and growth. 42,43 Therefore, an orally available drug that can inhibit leukemia cell growth in the CNS without adverse effects is desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in children and young adults, there are late effects of IT chemotherapy and CRT on cognition and growth. 42,43 Therefore, an orally available drug that can inhibit leukemia cell growth in the CNS without adverse effects is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in children and young adults, there are late effects of IT chemotherapy and CRT on cognition and growth. 42,43 Therefore, an orally available drug that can inhibit leukemia cell growth in the CNS without adverse effects is desirable.Because of its structural similarity to imatinib mesylate, which is a substrate for P-gp, 30 we first investigated whether INNO-406 was also a substrate for P-gp. The present study clearly demonstrated that INNO-406, like imatinib mesylate, is a substrate for P-gp ( Figure 1B-F).…”
mentioning
confidence: 99%
“…The results of the HR radiation randomization have been reported previously. 10 Nonrandomized changes to Protocol 95-01, also designed to reduce toxicity compared with previous protocols, included a reduction in the number of doses of asparaginase during the consolidation phase (20 instead of 30 consecutive weekly doses) and a reduction in the cumulative dose of doxorubicin for HR patients (300 mg/m 2 instead of 360 mg/m 2 ). In addition, National Cancer Institute (NCI) age and leukocyte criteria were applied prospectively in Protocol 95-01.…”
Section: Introductionmentioning
confidence: 99%
“…22 A randomized trial showed that hyperfractionated (twice daily) cranial irradiation failed to reduce neurocognitive late effects and might have compromised antileukemic efficacy, as compared to conventionally dosed radiation. 23 Two pediatric and at least two adult trials have tested the feasibility of omitting cranial irradiation in all patients. 12,[24][25][26] In the pediatric trials, the cumulative risks of isolated CNS relapse were 4.2% and 3.0%, and the rates of any CNS relapse (including combined CNS and hematological relapse) were 8.3% and 6.0%.…”
Section: Cranial Irradiationmentioning
confidence: 99%